Contemporary feminist theories - Jackson, Stevi; Jones, Jackie (Edinburgh University Press, 1998)
This textbook introduction to current feminist theories maps the development of feminist thought and suggests future directions. Reflecting the diversity of feminist theory, and its multiple practices and approaches, the chapters range across the humanities and social sciences covering: social theory; theory and economic change; political theory; jurisprudence;anthropological theory; psychoanalytic theory; theories of gender; lesbian theory; postmodern and cultural theory; black theory; literary theory; linguistic theories; media and film theory; postcolonial theory; perspectives on science; theorising the personal; methodologies/epistemologies; and women's studies.